FOTOREDUKSI ION Ag(I) DARI LIMBAH FOTOGRAFI DENGAN ASAM ORGANIK UNTUK RECOVERY PERAK - , Rr. Cininta Dwitya Paramita, Prof. Dr. Endang Tri Wahyuni, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The silver recovery from photographic wastewater by photoreduction of Ag(I) in the presence of organic acids of radiology division in Balai Pengobatan Penyakit Paru-Paru (BP4) Yogyakarta has been conducted. In addition, flowing N2 gas was also carried to prevent the oxidation of silver from photoreduction process. The amount of reduced Ag (I) was calculated by substracting the initial concentration of Ag(I) in the concentration of unreducted. The unreducted Ag(I) was measured by AAS. Identification of photoreduction products was performed by using X-Ray Diffraction (XRD) and Transmission Electron Microscopy (TEM). The result showed that photographic wastewater contains 99,54 mmol/L Ag(I) ions as [Ag(S2O3)2]3- complex. The highest photoreduction of Ag (I) was retained by using oxalic acid, followed by malonic acid and succinate acid. The photoreduction of Ag(I) retained highest results by using 0.5:1 of mol ratio. Nitrogen gas to achieve optimum photoreduction was 30 L. The product was solid materials containing S, Ag2S, Ag2O3, and Ag3O4. Furthermore, the addition of nitrogen could reduce the concentration of Ag2O3, Ag3O4 and increase of Ag formed.